2017
DOI: 10.1063/1.5007081
|View full text |Cite
|
Sign up to set email alerts
|

Rapid identification of pathogens responsible for necrotizing fasciitis on an integrated microfluidic system

Abstract: Necrotic fasciitis (NF) is a particularly aggressive and serious infection of the fascia that can penetrate into the musculature and internal organs, resulting in death if not treated promptly. In this work, an integrated microfluidic system composed of micropumps, microvalves, and micromixers was used to automate the detection of pathogens associated with NF. The entire molecular diagnostic process, including bacteria isolation, lysis, nucleic acid amplification and optical detection steps, was enacted on thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Despite these diagnostic scoring systems, clinical experience has shown that the diagnosis of NF relying solely on the above serological indicators is still insufficient and does not focus on the pathogenetic characterization of the trauma; therefore, some researchers have developed an integrated microfluidic system consisting of micropumps, microvalves, and micromixers, 48 which allows for the rapid identification of four pathogens (Vibrio vulnificus, Aeromonas hydrophila, and methicillin‐sensitive and resistant Staphylococcus aureus) associated with NF (within 90 min). Then by combining other methods for early diagnosis of NF, the accuracy of early diagnosis of NF was improved.…”
Section: Diagnostic Criteria Based On Clinical Manifestation and Labo...mentioning
confidence: 99%
“…Despite these diagnostic scoring systems, clinical experience has shown that the diagnosis of NF relying solely on the above serological indicators is still insufficient and does not focus on the pathogenetic characterization of the trauma; therefore, some researchers have developed an integrated microfluidic system consisting of micropumps, microvalves, and micromixers, 48 which allows for the rapid identification of four pathogens (Vibrio vulnificus, Aeromonas hydrophila, and methicillin‐sensitive and resistant Staphylococcus aureus) associated with NF (within 90 min). Then by combining other methods for early diagnosis of NF, the accuracy of early diagnosis of NF was improved.…”
Section: Diagnostic Criteria Based On Clinical Manifestation and Labo...mentioning
confidence: 99%